The Development of Scientific Literacy-Based English Teaching Materials For Biology Students - Syahreni Siregar; Eka Yuniasih (Universitas Cokroaminoto Palopo, 2022)
This study aimed to develop English teaching materials based science literacy for biology students and to determine the appropriateness of these teaching materials to be used in the learning process at the Biology students of IAIN Metro. This was a research and development (R & D). The steps of the research development model carried out include 6 steps, namely research and collecting the data, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision. Based on the results of the research, it can be concluded that the development of English teaching materials can be integrated with Biology so that it can support English Language Lectures in the Biology Education Department, as well as differentiating English in the Biology department and other departments. The teaching material entitled